PENJUAL KEDONDONG DAN KERIPIK PISANG DI UNIVERSITAS SAM RATULANGI MANADO - Manutty, Melinda A. (Universitas Sam Ratulangi, 2016)
The informal sector are also found at the University of Sam Ratulangi, they sold drinks and snacks in all the faculty. Marketers this trading at a gate or on the cusp of arround campus, bananas green ice, coconut young ice, Opa Alex jelly ice , meatballs, kedondong, crisps bananas etc. They sold huckster at the University of Sam Ratulangi by means of a huckster will carry them in front of the breastbone those who placed inside a small basket tied by a drawstring plastic and was hanged in their necks. They walked went around campus to peddle their trading up even often we see them until the afternoon. Almost all the seller kedondong and chips this mobile were children who dropped out of school, between the ages of 12-26 years, they comes from the town of Gorontalo come try their luck in Manado hopes to get a bite of rice. But to be a seller of kedondong not required qualification and appearance interesting, are especially only a willingness to work without shame and prestige. There are two factors causing they choose to into sellers kedondong, because dropouts so they do not have requested qualification as conditions must in search of work, and secondly because the economy family who cannot so they choose to wander and jobs to help their parents. Keywords: crisps, snack, seller